Female Reproductive Strategies of Marine Fish Species of the North Atlantic - Murua, Hilario; Saborido-Rey, Fran (Northwest Atlantic Fisheries Organization, 2003)
9 páginas, 2 figuras, 2 tablas. This contribution describes and identifies the most common reproductive strategies of a large number of commercially important fish species of the North Atlantic with regard to oocyte development, ovary organization, recruitment of oocytes and spawning pattern. Group-synchronous ovary organization, determinate fecundity and batch spawning was the most common suite of associated reproductive traits observed among North Atlantic fishes (e.g., gadoids, pleuronectoids). Another common type of female reproductive strategy among these species was synchronous, determinate and total spawning which occurred in a number of semelparous (eels, Anguilla sp., capelin, Mallotus villosus) and iteroparous species (e.g., redfishes, Sebastes sp., monkfishes, Lophius sp., herring, Clupea harengus, and elasmobranchs). Asynchronous, indeterminate and batch spawning occurred among anchovies, Engraulis sp., European hake, Merluccius merluccius, mackerels, Scomber sp. and Trachurus sp., swordfish, Xiphias gladius, and others. Categorization of species according to reproductive strategy assists in the estimation of species-specific fecundity and reproductive potential using various developed protocols. Peer reviewed